Good Pregnancy Outcome in a Triplet Pregnancy After Fetal Reduction due to Down Syndrome in the Second Trimester and a Delayed-Interval Delivery in the Third Trimester - Yu-Hung Tung; Kuang-Wei Chen (Elsevier, 2004)
Objective: Triplet pregnancies have a high risk of preterm delivery, and the incidence of chromosomal anomalies is higher than that of singletons. Abnormal fetuses should be diagnosed and properly reduced to prevent preterm delivery of the remaining fetuses. Case Report: A 36-year-old female was unable to conceive due to male factor infertility. After treatment with a long protocol of buserelin therapy, in vitro fertilization, and tubal embryo transfer, she achieved a triplet pregnancy. She underwent amniocentesis because of her advanced age; it was determined that one of the triplets had translocation Down syndrome. Under ultrasound guidance, we performed selective termination of the affected fetus at 20 weeks' gestation. The patient developed preterm uterine contractions at 31+4 weeks' gestation and was hospitalized. She spontaneously delivered a fetus papyraceous at 33+1 weeks' gestation. Three days later, interval delivery was performed and the two remaining fetuses were delivered in good condition by cesarean section. Conclusion: The risk of fetal chromosomal anomalies is increased in multiple pregnancies. Abnormal fetuses can be diagnosed using amniocentesis and selectively terminated safely. Delayed-interval delivery can be used to improve the outcome for the remaining fetuses.